Management of Higher Educational Institutions Based On Alwashliyahan At Univa Medan - Akhir, Muhammad; Mesiono, Mesiono; Ritonga, Asnil Aida (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The purpose of this writing is to analyze: 1) Institutional planning for religious affairs-based higher education at UNIVA Medan; 2) Organizing religious-based higher education institutions at UNIVA Medan; 3) Direction of Islamic-based higher education institutions at UNIVA Medan; 4) Leadership of Islamic-based higher education institutions at UNIVA Medan; and 5) Supervision of religious-based higher education institutions at UNIVA Medan. The research method used in this research is a qualitative research method, where the results obtained in this research are: 1) Value-based planning consisting of universal values, Islamic values, and kealwashliyahan. Making the values of worship and mumtaz as basic values, establishing the vision of mumtaz, improving infrastructure, accreditation, spirituality, opening postgraduate studies, digitalization, university identity, RIP, research university, WCU, GUG, development of KKNI + ma'had aly, as well as the development of Tri Dharma into Catur Dharma; 2) Value-based organizing consisting of universal values, Islamic values, and religious beliefs. Organizing is carried out by setting common goals, professional and proportional, fit and profitable, and building trust; 3) Value-based guidance consisting of universal values, Islamic values, and religious beliefs. 3T+1H directing method, direct involvement, coordination, determination of technical guidelines, community unity, focus on goals, Tri Dharma and Catur Dharma; 4) Value-based leadership consisting of universal values, Islamic values, and kealwashliyyah. Leaders must have competence, emulate the leadership of the Prophet, motivation, and apply digital leadership, and 5) Value-based supervision consisting of universal values, Islamic values, and religious beliefs. Supervision is carried out using a dual system consisting of internal and external, involvement of the parent organization, supervision of Tri Dharma & Catur Dharma, as well as supervision based on katauhidan values.